A case report of acute heart failure, pulmonary edema, and pleural effusion in an elderly patient with organic mental disorder - Guohui Jiao; Yongcai Wu; Shanshan Zhang; Haiyan Wang; Xiaoli Du (Medicine, 2026)
Rationale: Organic mental disorders complicate acute heart failure (AHF) in elderly patients, creating a heart–brain vicious cycle in which cognitive impairment masks cardiac symptoms while hypoxemia worsens delirium. Holistic nursing offers an integrative solution to this multidimensional complexity. Patient concerns: A 67-year-old male with a 5-year history of visual hallucinations, insomnia, and poorly controlled hypertension presented with generalized edema and severe dyspnea. On admission, oxygen saturation was 60% (85% with oxygen), blood pressure was 139/90 mm Hg, and bedside ultrasound revealed bilateral pleural effusions (86 mm and 122 mm). Diagnosis: Organic mental disorder, AHF (New York Heart Association class IV), bilateral pleural effusion, pulmonary edema. complete left bundle branch block, hypertension stage 2, hepatic impairment, hypoproteinemia, and hypochloremia. Interventions: Holistic nursing included continuous triad assessment of consciousness, respiration, and circulation; low-flow oxygen and semi-recumbent positioning; nitroglycerin and furosemide with dynamic adjustment; ultrasound-guided thoracentesis with 660 mL drainage; daytime cognitive orientation; nighttime 3 mg zopiclone; precise volume management maintaining 400 to 500 mL negative daily balance; high-protein nutrition; and bundled infection control. Outcomes: After 16 days, dyspnea and edema resolved, pleural effusions cleared, and ejection fraction improved. Orientation was restored, weight fell from 65 kg to 53.8 kg, and no nosocomial infections occurred. At 3-month follow-up, vitals were stable, the patient was adherent to medications and self-sufficient, with no recurrence of AHF or psychiatric symptoms. Lessons: Holistic nursing effectively manages cardiopulmonary-psychiatric comorbidities through multidimensional assessment and multidisciplinary collaboration. Strengthening discharge planning and hospital-community continuity is essential.